PEMBEKALAN ATAS FENOMENA PRE-POST PERNIKAHAN USIA DINI DI KAMPUNG CIBUYUTAN - Septyan, Krisno; Wiryanto, Fadhli Suko (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Servants receive complaints from community leaders in Cibuyutan village about the phenomenon of early marriage. The purpose of the community service program is to provide debriefing to the community to continue education for those who are not married and household conflict management for those who are married. The method used is in the form of lectures. The provisional result of this community service based on directives from the local Environmental Chair and madrasa teachers is that the achievements have been fulfilled by providing the message to be conveyed at an early age. This process needs to be done to give a message that will be embedded in the subconscious that education is important to produce a better civilization.